Community Participation in Primary Healthcare in the South Sudan Boma Health Initiative: A Document Analysis - Loubna Belaid; Iván Sarmiento; Alexander Dimiti; Neil Andersson (Kerman University of Medical Sciences, 2022)
Background  Community participation is central to primary healthcare, yet there is little evidence of how this works in conflict settings. In 2016, South Sudan's Ministry of Health launched the Boma Health Initiative (BHI) to improve primary care services through community participation.Methods  We conducted a document analysis to examine how well the BHI policy addressed community participation in its policy formulation. We reviewed other policy documents and published literature to provide background context and supplementary data. We used a deductive thematic analysis that followed Rifkin and colleagues' community participation framework to assess the BHI policy.Results  The BHI planners included inputs from communities without details on how the needs assessment was conducted at the community level, what needs were considered, and from which community. The intended role of communities was to implement the policy under local leadership. There was no information on how the Initiative might strengthen or expand local women's leadership. Official documents did not contemplate local power relations or address gender imbalance. The policy approached households as consumers of health services.Conclusion  Although the BHI advocated community participation to generate awareness, increase acceptability, access to services and ownership, the policy document did not include community participation during policy cycle.